Observed variability in the current field during summer monsoon experiments: Arabian Sea - RAO, R.R.; SANIL KUMAR, K. V.; MATHEW, BASIL (MAUSAM, 1996)
The observed short term variability in the current field of the upper layers at selected locations in the Arabian Sea is examined utilising the available short (1-2 weeks) time series of moored currentmeter records obtained from former USSR stationary ship polygons during MONSOON-77 and MONEX-79 field experiments. Supplementary time series data sets on surface wind, sub-surface temperature and salinity were also made use of to explain the observed structure and variability of current field, in the upper 2OOm water column. The thermal regime in the central Arabian Sea showed cooling and deepening of the surface mixed layer with the onset and progress of the summer monsoon during MONSOON- 77 while the corresponding variability was marginal in the western and south-central Arabian Sea during pre-onset regime of MONEX-79, The Ekman balance appeared to be limited to the mixed layer, only during pre-onset regime of MONSOON-77 and was absent during pre-onset and onset regimes of MONEX-79 suggesting the importance of internal ocean dynamics influencing the current field. Most of the current records showed rich structure with superposed oscillations extending over the entire 200m water column. During progress regime of MONSOON-77 and at the equatorial station during pre-onset regime of MONEX-79. dramatic reduction in the current strength is noticed from mixed layer to thermocline due to differences in the eddy viscosity. During MONEX-79, a strong subsurface core of southerly flow ( -100 cm/s) was noticed at the equator (49°E) even before the onset of monsoon. The vector time series of current-meter records subjected to rotary spectral analysis showed inertial oscillations in the flow regime more prominently during MONSOON-77 as compared to MONEX-79. R.R. RAO. K. V. SANIL KUMAR123@gmail.com and BASIL MATHEW123@gmail.com